Investigation of moisture content and higher heating value in refusederived fuel from agricultural residues using statistical modelling - Ny, Abd Halim; Noor Intan Shafinas, Muhammad (AIMS Press, 2025)
There is an increasing interest in using agricultural residues and wastes for energy production due to concerns regarding climate change and energy security issues. One of the alternative fuels considered is Refuse-derived fuel (RDF) from biomass, which has a Higher Heating Value (HHV) comparable to coal. This study aims to investigate the relationship between the moisture content and the HHV value. Palm kernel shells (PKS), coconut husks (CH), and coconut shells (CS) were blended at various ratios (10%–80%) and moisture levels (5%, 7%, 10%). The HHV was analyzed through a proximate analysis, with JMP Pro 17.0 modelling the HHV against the moisture content. Then, the Tukey-Kramer analysis identified the optimal energy ratio, thus providing insights into maximizing the RDF efficiency. The result showed that the highest HHV was 21.617 MJ/kg with the RDF2 formulation. Notably, the RDF2 energy content was less than 4% of that of coal, thus demonstrating the potential of utilizing agricultural waste to produce solid fuel with a positive environmental impact.